Seismicity and Ground Motion Simulations of the SW Iberia Margin - Bezzeghoud, M. (2010)
In this study, we focus on the region between Gorringe Bank and the Horseshoe Fault located in the SW Iberia margin, which is believed to be the site of the great 1755 earthquake. We model ground motions using an extended source located near the Horseshoe scarp to generate synthetic waveforms using a wave propagation code, based on the finite-difference method. We compare the simulated waveforms using a 3-D velocity model down to the Moho discontinuity with a simple 1-D layered mod- el. The radiated wave field is very sensitive to the velocity model and a small number of source parameters; in particular, the rupture directivity. The rupture directivity (controlled by the rupture initiation location), the strike direction and the fault di- mensions are critical to the azimuthal distribution of the maximum amplitude oscilla- tions. We show that the use of a stratified 1-D model is inappropriate in SW Iberia, where sources are located in the oceanic domain and receivers in the continental do- main. The crustal structure varies dramatically along the ray paths, with large-scale heterogeneities of low or high velocities. Moreover, combined with the geometric li- mitations inherent to the region, a strong trade-off between several parameters is of- ten observed; this is particularly critical when studying moderate magnitude earth- quakes (M< 6), which constitute the bulk of the seismic catalogue in SW Iberia.